Legal Protection Against Rape Victims Based On Victimology - Asliani Asliani (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to find out the legal protection for victims of rape, to find out the protection of Victims in terms of victimology, and to find out the obstacles in the protection of rape Victims. Based on the nature of the research, The research leads Juridical normative legal research that is research Aimed at analyzing the rules of law regulations. The basic idea of protection against rape Crime Victims is due to the Suffering experienced by rape crime viktims and does not require a short amount of time to be Able to recover them, so law enforcement Officials are obliged to provide protection against rape Victims who are implemented to the legislation as legal products in favor of the victim. Protection of the Victims of rape in terms of victimization that the victim is still treated as an object, not a subject that must be heard and respected in his legal rights. The mostly still the make women victim of rape victim a second time (revictimization) for the cases the experienced. Victims are still Often blamed and not given as much protection as what is needed, namely about assistance by a psychologist to recover mentally and traumatized over Incidents of rape. Constaints in the protection of rape Victims in terms of victimization are internal and external barriers. Internal barriers in the form of the many parties Involved from various institution and the extent of funding activivites create Difficulties in conducting supervision of the implementation of each activity. While the external obstacle is the bureaucracy that is related to not being a priority issue that is brought up among policy makers.